2001
DOI: 10.1111/j.1471-0528.2001.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peritoneal factors on port‐site metastases in a xenograft ovarian cancer model

Abstract: Objective We determine the main physical effects of pneumoperitoneum on tumour dissemination and port-site metastases occurrence.Design A prospective randomised study in rats.Methods A human ovarian cancer cell line (IGR-OV1) was xenografted in nude rats. Seven days after cancer inoculation, surgery was performed. Rats were randomised in two main groups and underwent either: gasless laparoscopy (n 20) CO2 laparoscopy with pneumoperitoneum pressure at 4 mmHg (n 20), or 8 mmHg (n 20) with in each case, increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…In in-vitro experiments, the SKOV3 ovarian carcinoma cell line was found to show increased growth under the influence of CO 2 [8]. By contrast, in various studies in which the nude rat model was used, neither the laparoscopy gas used nor laparoscopy itself was found to have any influence on various tumor parameters such as the weight of the omentum, metastases, survival of the animals or circulating tumor DNA, in comparison with laparotomy [5,9,10,11,12]. However, Canis et al [6] observed increased tumor growth after laparotomy in the BD IX rat model in comparison with animals that underwent laparoscopic procedures.…”
Section: Discussionmentioning
confidence: 91%
“…In in-vitro experiments, the SKOV3 ovarian carcinoma cell line was found to show increased growth under the influence of CO 2 [8]. By contrast, in various studies in which the nude rat model was used, neither the laparoscopy gas used nor laparoscopy itself was found to have any influence on various tumor parameters such as the weight of the omentum, metastases, survival of the animals or circulating tumor DNA, in comparison with laparotomy [5,9,10,11,12]. However, Canis et al [6] observed increased tumor growth after laparotomy in the BD IX rat model in comparison with animals that underwent laparoscopic procedures.…”
Section: Discussionmentioning
confidence: 91%
“…Several investigations have shown that a deficient supply of blood and oxygen in ascites provides favorable conditions for the growth and survival of tumor stem cells 3940. Indeed, the presence of malignant ascites during and after surgery has been reported to increase the risk of port-site metastasis 12. Another reason may be that tumor cells in the ascitic fluid flow easily into the port site during the B-ultrasound-guided or laparoscopically-assisted placement of catheters for HIPPC.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have been raised in light of numerous case reports documenting port-site recurrences after diagnostic laparoscopy or laparoscopic resection in patients with malignancies,678910 and these concerns have limited the use of laparoscopic techniques for the resection of intra-abdominal malignancies. Therefore, further studies of the factors contributing to port-site metastasis are needed to overcome this serious problem 11121314…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Подобные сведения инициировали проведение различных экспериментальных исследований, направ-ленных на изучение патогенеза этих явлений и подтвер-дивших на животных моделях обоснованность опасений специалистов, предопределив критическое и насторожен-ное отношение к видеоэндоскопической хирургии, со-храняющееся во многих онкологических школах и по сей день [6][7][8]. Тем не менее анализ накопленного к настоя-щему времени опыта позволяет более объективно оценить обсуждаемую проблему.…”
Section: Discussionunclassified